Design of orthogonal genetic switches based on a crosstalk map of σs, anti‐σs, and promoters - Virgil A Rhodius; Thomas H Segall‐Shapiro; Brian D Sharon; Amar Ghodasara; Ekaterina Orlova; Hannah Tabakh; David H Burkhardt; Kevin Clancy; Todd C Peterson; Carol A Gross; Christopher A Voigt (Molecular Systems Biology)
Abstract Cells react to their environment through gene regulatory networks. Network integrity requires minimization of undesired crosstalk between their biomolecules. Similar constraints also limit the use of regulators when building synthetic circuits for engineering applications. Here, we mapped the promoter specificities of extracytoplasmic function (ECF) σs as well as the specificity of their interaction with anti‐σs. DNA synthesis was used to build 86 ECF σs (two from every subgroup), their promoters, and 62 anti‐σs identified from the genomes of diverse bacteria. A subset of 20 σs and promoters were found to be highly orthogonal to each other. This set can be increased by combining the −35 and −10 binding domains from different subgroups to build chimeras that target sequences unrepresented in any subgroup. The orthogonal σs, anti‐σs, and promoters were used to build synthetic genetic switches in Escherichia coli. This represents a genome‐scale resource of the properties of ECF σs and a resource for synthetic biology, where this set of well‐characterized regulatory parts will enable the construction of sophisticated gene expression programs.